2021
DOI: 10.3892/or.2021.7926
|View full text |Cite
|
Sign up to set email alerts
|

IL‑6 plays a crucial role in epithelial‑mesenchymal transition and pro‑metastasis induced by sorafenib in liver cancer

Abstract: Interleukin-6 (IL-6) is involved in various biological responses, including tumor progression, metastasis and chemoresistance. However, the role and molecular mechanism of IL-6 in the treatment of sorafenib in liver cancer remain unclear. In the present study, through western blot analysis, Transwell assay, flow cytometric assay, ELISA analysis and immunohistochemistry it was revealed that sorafenib promoted metastasis and induced epithelial-mesenchymal transition (EMT) in liver cancer cells in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 49 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…It also sheds light, at least in part, on the underlying mechanisms of EMT associated with IL-6 in CRC cells. Several in vivo studies have shown that the IL-6 knockdown could attenuate tumor metastasis in mice models [ 65 ], while IL-6 over-expression has also been validated with enhancing head and neck tumor growth and EMT change, eventually leading to tumor metastasis to the lung site [ 46 ]. Given these existing studies that IL-6 indeed alters EMT change in mice tumor models and leads to tumor metastasis, future efforts will be made to develop the co-culture system of CRC cell lines with immune cells as macrophages or stroma cells to mimic the IL-6 secreting TME system and elaborate to its consequence of CRC EMT change.…”
Section: Discussionmentioning
confidence: 99%
“…It also sheds light, at least in part, on the underlying mechanisms of EMT associated with IL-6 in CRC cells. Several in vivo studies have shown that the IL-6 knockdown could attenuate tumor metastasis in mice models [ 65 ], while IL-6 over-expression has also been validated with enhancing head and neck tumor growth and EMT change, eventually leading to tumor metastasis to the lung site [ 46 ]. Given these existing studies that IL-6 indeed alters EMT change in mice tumor models and leads to tumor metastasis, future efforts will be made to develop the co-culture system of CRC cell lines with immune cells as macrophages or stroma cells to mimic the IL-6 secreting TME system and elaborate to its consequence of CRC EMT change.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, sorafenib increased the IL-6 expression in HCC cells and promoted metastasis and EMT progression in HCC cells. Knockdown of IL-6 could significantly decrease sorafenib resistance in HCC cells [ 97 ]. IL-6 is one of the pro-inflammatory cytokines secreted by TAMs, and sorafenib was shown to induce IL-6 secretion by TAMs [ 57 , 58 ].…”
Section: Tkis-induced Tme Remodelingmentioning
confidence: 99%
“…The ability of IL-6 to trigger an EMT and enhance cancer cell motility has been extended to colorectal cancer, cancer stem cells in blood vessels in head and neck squamous cell carcinomas, hepatocellular cancer, and laryngeal squamous cell carcinoma [ 51 , 52 , 53 , 54 ]. The ability of IL-6/STAT3 to modulate additional tumor-promoting and tumor-suppressing pathways have been extensively investigated [ 11 , 51 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Il-6 Triggers Enhanced Cell Motility and An Epithelial To Me...mentioning
confidence: 99%